APDL Modeling Method of Accurate Mesh Model of Helical Gear - Tan Jun; Gao Defang; Yang Chao (Jixie chuandong)
To solving the problem that it is difficult to build an accurate solid model of meshing helical gears in ANSYS,a new parameterized approach to building an accurate solid model of meshing helical gear based on APDL is presented. The solid model of helical gear pair is built at the reference position based on the equations of the tooth profile curve equation. Taking the meshing position that helical gear pair has the minimum total length of contact lines as the initial meshing position,the rotational phase from the reference position to the initial meshing position of helical gear pair is determined,the initial solid model of meshing helical gears is built by rotating the helical gear pair based on the rotational phase. The equation of phase change in one contact lines distribution change cycle of meshing helical gears is established,then,the every meshing position of meshing helical gears in one contact lines distribution change cycle can be caught by the control of the meshing phase factor in the equation. The results of numerical experiment show that the meshing solid model of helical gear generated by the presented method has a good geometric precision,which can guarantee that the simulation results is credible.